Ankle Fractures in Children - Samena Chaudhry; K Dehne (Open Journal of Trauma - Peertechz Publications, 2019)
Ankle Fractures in the paediatric population are among the most common physeal injuries. Trauma around the ankle often results in distal tibial metaphyseal fractures in the very young child, medial and lateral malleolus fractures in middle childhood (McFarland fractures) and transitional fractures in adolescence (Tillaux and Triplane fractures). Factors affecting treatment decisions include the Salter Harris classifi cation, the age of the child and intra-articular involvement.